VOCABULARY OPTIONS OF POWER EXPERIENTIAL VALUE OF BUGIS FEMALE TEACHER IN INDONESIAN LANGUAGE SUBJECT - Asri Ismail; Anang Santoso; Sunoto Sunoto (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
This article reviews the vocabulary options in the experiential values of Bugis female teachers in teaching Indonesian language in the classroom. In this research, teacher's speech in teaching is seen as a verbal interaction that becomes the estuary of authorization. These authorities power are traced through the vocabulary choices seen in the experiential value. In the text, the discourse analysis model used Norman Fariclough model, the vocabulary. Vocabulary choice seen from the experiential value found convincing, domination, and control vocabularies. The results found that the resistance of Bugis female teachers in class discourse was a dissatisfaction form of the patriarchal tradition prevailing in society.